The Role Of Artificial Intelligence In Enhancing Business Innovation And Creativity In The Cosmetics Industry Of Dubai - Ullah, Khalil; Hardjono, Retno Kusumastuti (Universitas Diponegoro, 2024)
The role that artificial intelligence can play in enhancing business innovation and creativity in the cosmetic industry in Dubai is considered. Amongst many key factual problems faced by this industry, there is personalization, supply chain optimization, formulation of products, marketing, and branding—issues that remain ethical and private. The conceptual problems addressed are related to the balance between creativity and automation, data quality, and bias, interdisciplinary collaboration, and change management.It aims to understand how AI-powered solutions can contribute to addressing these challenges and serve as a driver of innovation in the cosmetics sector of Dubai. This paper considers previous related literature about AI applications in multiple business functions and some conceptual framework that links AI to creativity and innovation. In this regard, a mixed-method approach will utilize questionnaires, interviews, and case studies to analyze the interlinkages between AI adoption, AI capabilities, data-driven decision making, and cognitive augmentation as they influence firm innovation and creativity.The research is likely to be of benefit to Dubai Cosmetics Firms with critical insights; at the same time, it will complement existing literature on how emerging technologies can help instill innovation in business activity.